Evolution of Wilshire equations for creep life prediction - Mark Whittaker (Materials at High Temperatures, 2014)
In the past decade, a new approach to predictive creep lifing has been developed, known as the Wilshire equations. Having been applied to a range of power generation and aerospace materials, the understanding of material behaviour associated with the equations has developed significantly. With the equations based around the dominance of diffusion controlled dislocation movement for creep deformation under typical engineering stresses and behaviours, the predictions made are related to microstructural phenomena, such as the onset of yield. The current paper seeks to review the application and development of the Wilshire equations, with suggestions for future research in the area.